Determination of tylosin residues in animal tissues by HPLCPDA. - TSIGOURI (Α.Δ. ΤΣΙΓΟΥΡΗ) A. D.; TYRPENOU (Α.Ε. ΤΥΡΠΕΝΟΥ) A. E.; GOUTA (E.H. ΓΟΥΤΑ) E. H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Tylosin belongs to the group of macrolide antibiotics and is widely used both therapeutically against Gram-positive microorganisms and Mycoplasma spp. and as a feed additive for growth promotion. In the European Union, according to Regulation 1442/95, tylosin residues of up to 100 μg/kg are permitted in the edible tissues of slaughter animals. For the determination of tylosin residues in meat and kidney samples a modification of the method of Chan et al. (1994) has been applied. The method is simple, rapid and accurate. Tylosin extraction is carried out with acetonitrile combined with phosphate buffer (pH 2.5) and extract eleanup is performed using BondElut C18 s.p. cartridges. Tylosin is luted with 0.1 M ammonium acetate in methanol. The determination is accomplished by RP-HPLC with UV detection at 287 nm. The LC separation is carried out on a Symmetry C18 column (150x3.9 mm, 5μ) using a mobile phase of 0.1M ammonium formate (pH 5.0) / acetonitrile (70/30) at a flow rate of 0.8 ml/min. Positive results are easily confirmed by spectra comparison. The recovery achieved was 86.70±0.95% and the limit of determination 40 μg/kg. Diluted standards and sample extracts are stable for 3 weeks if kept at -20 °C.